Enabling Consumer and Entrepreneurial Literacy in Subsistence Marketplaces - Viswanathan, Madhubalan; Gajendiran, S.; Venkatesan, R. (Education in the Asia-Pacific Region: Issues, Concerns and Prospects, 2008)
This book describes research on low-literate, poor buyers and sellers in subsistence marketplaces, the consequent development of an innovative marketplace literacy educational program that enables consumer and entrepreneurial literacy, and implications of the research and the educational program for business, education, and a variety of disciplines and functions. There are two important resources that individuals living in subsistence need to function in the economic realm: finances and know-how. The book describes an educational program that focuses on enabling generic skills about the marketplace. This program uses the "know-why" or an understanding of marketplaces as a basis for the know-how of being an informed buyer or seller. This volume discusses implications of the research and the educational program for non-profit organizations, for research and practice in education, for business research and practice, and for academic and applied research.